First ontogenesis and bioecological study of Sciobia bouvieri (Orthoptera, Gryllidae), a North African endemic species - Naima, Adjou; Ahlem, Meriem; Salaheddine, Doumandji (Zootaxa, 2024)
This study aimed to investigate the bioecology and life cycle of the Algerian endemic Sciobia bouvieri, which remained unknown until recently. A combined approach of field sampling through direct searching and captive rearing of S. bouvieri nymphs under natural conditions was employed to determine the population ontogeny. The life cycle was found to comprise three stages: egg, nymph, and adult. The embryonic development period ranged from 22 to 30 days. Females laid an average of 9.4 ± 1.3 eggs per clutch. The nymphal stage consisted of six instars, lasting an average of 306.5 days. Adult longevity varied, with males living 32.3 ± 16.2 days and females living 23.9 ± 22.4 days. The duration of the ontogenesis cycle of Sciobia bouvieri in nature showed that it has a univoltine life cycle with summer and winter diapauses occurring during the fourth and fifth larval stages, respectively. These diapauses are likely controlled by photoperiod and temperature. This is the first study of the bioecology and life cycle of this North African endemic species.